MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN PENERAPAN STRATEGI PEMBELAJARAN KONTEKSTUAL SISWA KELAS VIIIB MTs NEGERI 1 MERANGIN - Hellinawati (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The purpose of this classroom action research is to improve the mathematics learning outcomes of Class VIII B students at MTs Negeri 1 Merangin by applying contextual learning”. Judging from the results of the Final Semester Exams (UAS) for Class VIII MTs Negeri 1 Merangin students for the last three years in a row, the data is still high in the percentage of students who score below the Minimum Completeness Criteria (KKM). This cannot be allowed to continue without the handling of a teacher. Teachers need to evaluate what factors cause this to happen. The trend in the new paradigm of education is that learning is better if the learning environment is created naturally. Contextual Learning Strategy is one suitable choice to be applied. This research is a Classroom Action Research (CAR), because according to Sukmadinata (2010: 140) action research is a systematic search action carried out by the implementers themselves (in education it is carried out by teachers, lecturers, school principals, counselors). This PTK lasted for two cycles. The action plans for each cycle in this CAR are divided into four activities, namely; (1) planning, (2) action implementation, (3) observation and evaluation, and (4) analysis and reflection. From the results of the analysis of observational data and student learning outcomes data as well as the results of the discussion, it can be concluded as follows: 1) Contextual learning strategies can improve student learning activities in class VIII B MTs Negeri 1 Merangin. 2) The application of contextual learning strategies can improve student learning outcomes in class VIII B MTs Negeri1 Merangin on the material of Functions and Graphs of Functions